Diasystematic information in learner’s dictionaries: the usability of multiple labels - Marjeta Vrbinc; Alenka Vrbinc (Penerbit UKM, 2015)
Labels in dictionaries provide information about restrictions and constraints on the use of certain words or senses in the contexts in which they occur or in relation to other words described in a dictionary. These restrictions are referred to as diasystematic information. This contribution deals with diasystematic information in four British monolingual learner‟s dictionaries (OALD8, LDOCE5, CALD3, and MED2) with the emphasis on multiple labels. A detailed classification of labels is presented and an in-depth overview of labels used in combination with one another in the dictionaries under investigation is given. Then follows a discussion of labels which are often used in combination, the aim being to establish whether labels belonging to one and the same category combine with one another or whether multiple labelling consists of labels from different categories of labels. The findings of this study show that labels belonging to different groups are mostly combined, and apart from that, labels expressing diaevaluative information and those expressing diastratic information can be combined within the group. Possible reasons for this are discussed in the contribution. The inclusion of diasystematic information largely depends on the type of dictionary and especially on its intended users. Therefore, lexicographers‟ decisions about whether to use a label and how to use it appropriately should be based on the user profile. This is especially true of monolingual learner‟s dictionaries, where one of the main functions is to promote the active use of a foreign language where every single piece of information included in the dictionary counts.